Conocimiento logístico y su relación con el desempeño laboral del personal de la empresa AF Boullosa de Iquitos, periodo 2023 - Molano Garcia, Jean Pierre (2024)
Logistical knowledge is essential for personnel who work in those areas where it is necessary to carry out activities (planning, storing and distributing) related to the acquisition of goods and/or products (merchandise) until they reach their final destination (client) in a timely manner through the efficient use of the resources available to them; Furthermore, this knowledge they possess allows staff to improve their work performance, generating an increase in productivity. A research was developed entitled "Logistics Knowledge and its relationship with the Work Performance of the personnel of the company AF Boullosa of Iquitos, period 2023", and focuses on determining the relationship between the variables of the study (logistical knowledge and work performance). The research presents a quantitative study with a descriptive correlational design, using in this case the survey and questionnaire as a technique and instrument for obtaining data, said instrument was subjected to a reliability test and then applied to a population made up of 23 collaborators. Finally, the results indicate that there is an intense and significant positive relationship between the variables, according to the Pearson correlation coefficient, which was 0.638 and a degree of significance of 0.001.